The legal interest of the self-government community and its protection under Polish law - Krawczyk, Ryszard Paweł (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
In Poland, the concept of a self-governing community is a certain legal fiction, identified with all residents of units of basic administrative division. In Europe, a self-governing community is quite commonly called a local community. A self-government community in Poland is established by law and is a forced union of people. The community does not have its own legal personality separated from the legal peresonality of a local government unit. The author of the study discusses the constitutional and statutory concept of a self-governing community as well as system and legal solutions protecting its interest. The author analyzes the problem of protecting the interest of the self-government community, referring to the examples of Polish local government practice.